Study on Water Level Measurement System with ELWPsXT Sensors and Alert System through the Mobile Application - KHONGSOMBOON, Khamphong; INSANKEOVILAY , Souksamai; DIDTAPHONG, Xaysamone; SOULIYA, Bounta; SISAAT, Khamphao (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
Laos is a country where the Mekong River flows from the north to the south and there is a lot of rain during the rainy season. Usually, it can be observed that flood occurs every 1.4 years and it spreads to a wide range of area every 5.7 years, the information from Department of Meteorology and Hydrology, 2020. Every time there is a flood disaster or a typhoon, causing billions of kip in damage, causing economic damage, buildings, houses, and parks, or weakly constructed buildings will be destroyed by the flowing water. Transportation and communication routes may be cut off from time to time due to the force of the currents. Roads and bridges may be destroyed by the currents. Goods in transit may be damaged. For this reason, the Government has used billions of kip to help flood victims every year. Lack of readiness to prepare and prevent the occurrence of floods because the warning system is not up-to-date and not common. This research, therefore, proposed to examine the water level, temperature, and humidity measurement system with high accuracy using ELWPsXT and DHT22 sensors. The methodology is to bring the data obtained from the measurement from the sensor and store it in the memory that can store the data for months to years and then bring it through the calibration process with a linear equation compared to the standard water level. This system can also report the real-time information that can provide accurate information through the website and mobile phone app. The measured water level has an average difference of 4 millimeters when compared to the TeleData system of the Department of Meteorology and there will be an average difference of 1 millimeter and 4 millimeters when compared to the water level standard at high and low tide respectively. When we think about the maximum difference that may affect the report of floods, the measured value will be 2.5 centimeters. It is seen that the error value of 0.15% is very small compared to the value that can be read from the lake. The speed of sending and receiving data through the telephone network system will take an average of 14 seconds, with the highest value at 26.80 seconds and the fastest at 10.47 seconds. If compared with the 3-minute notification standard, it is seen to be almost 13 times faster. This information will be important in preparing for prevention and preparing to evacuate in the event of a disaster.